Prevalence and associated factors of anemia in a Russian population: the Ural eye and medical study - Mukharram M. Bikbov; Gyulli M. Kazakbaeva; Rinat M. Zainullin; Venera F. Salavatova; Timur R. Gilmanshin; Dilya F. Yakupova; Yulia V. Uzianbaeva; Inga I. Arslangareeva; Songhomitra Panda-Jonas; Svetlana R. Mukhamadieva; Renat I. Khikmatullin; Said K. Aminev; et al. (BMC, 2019)
Abstract Background Although anemia is one of the leading causes of the global burden of disease, information about its prevalence in Russia is mostly missing. We therefore assessed its prevalence and associated factors in a Russian population. Methods The population-based Ural Eye and Medical Study included 5899 (80.5%) out of 7328 eligible individuals (mean age:59.0 ± 10.7 years;range:40-94 years) who underwent a standardized interview and detailed general examination. The definition of anemia was based on the hemoglobin concentration (definition #1:hemoglobin concentration < 140 g/L in men,< 130 g/L in women; definition #2:hemoglobin concentration < 130 g/L in men,< 120 g/L in women [World Health Organization definition]). Results Higher hemoglobin concentration (mean:142.6 ± 14.8 g/L; range:80-171 g/L) was associated (multivariable analysis) with male gender (P < 0.001; standardized regression coefficient beta:-0.20), higher waist-hip circumference ratio (P < 0.001;beta:0.05), higher prevalence of car ownership (P < 0.001;beta:0.05), higher blood concentrations of bilirubin (P < 0.001;beta:0.05) and triglycerides (P < 0.001;beta:0.06), lower erythrocyte sedimentation rate (P < 0.001;beta:-0.32), and shorter blood clotting time (P < 0.001;beta:-0.39). Using definition #1 and #2, anemia was detected in 1385 individuals (23.6%;95% confidence interval CI)CI:22.5,24.7) and in 453 individuals (7.7%;95%CI:7.0,8.4), respectively. Prevalence of moderate anemia (hemoglobin concenttration:110 g/L-80 g/L), detected in 165 individuals (2.8%;95%CI:2.4,3.2), increased with younger age (P = 0.008;odds ratio (OR):0.98;95%CI:0.96,0.99), female gender (P < 0.001;OR:2.52;95%CI:1.47,4.33), higher erythrocyte sedimentation rate (P < 0.001;OR:1.08;95%CI:1.06,1.09), longer blood clotting time (P < 0.001;OR:8.56;95%CI:5.68,12.9), and marginally significantly, with a lower waist-hip circumference ratio (P = 0.058;OR:0.13;95%CI:0.02,1.07). In women, it was significantly (P < 0.001) higher before menopause (8.8%;95%CI:6.4,11.1) than after menopause (3.5%;95%CI:2.8,4.3). Conclusions In this Russian population as compared to populations from countries with a similar socio-demographic index, anemia prevalence was relatively low. As in other populations, higher anemia prevalence was strongly and inversely associated with menopause, and to a minor degree, with lower waist-hip circumference ratio and lower socio-economic background.